Music Pavilion, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Music Pavilion. Printed on verso: 89. Muisc Pavilion. This classic Temple of Music is finely embowered among forest trees and surrounded by flowers. In it famous bands discourse music, provided by the Exposition free, the concerts taking place several times daily. 1909. The Alaska-Yukon-Pacific Exposition. Official Photograph. Published by Robert A. Reid. 488 Arcade. Made in Seattle. PH Coll 777 Reid.89 (See also PH Coll 78.150) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number